MAN’S POTENTIAL OF NETWORK TECHNOLOGIES - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The phenomenon of man’s potential as a component of network technologies is analyzed.